Guideline Adherence of Post-Exposure Prophylaxis and Factors Associated with Vaccine Series Completion in Patients Presenting to the Emergency Department with Rabies-Risk Exposure - Ali Ekber Karabulut; Burcu Özen Karabulut (JOURNAL OF BIOTECHNOLOGY AND STRATEGIC HEALTH RESEARCH, 2026)
Objective: This study aimed to retrospectively evaluate adherence to national guidelines in rabies post-exposure prophylaxis (PEP) administered to patients presenting with rabies-risk exposures to the emergency department, and to identify factors associated with completion of the vaccine series.Methods: Records of 343 patients presenting to the Emergency Department of Ağrı Training and Research Hospital between June 2025 and May 2026 were reviewed. The distribution of continuous variables was assessed using the Shapiro-Wilk test; the Mann-Whitney U, Kruskal-Wallis, chi-square, and Fisher's exact tests were used for between-group comparisons. Adherence of the administered prophylaxis to the 2019 Turkish Ministry of Health Rabies Prophylaxis Guideline was evaluated.Results: The median age of patients was 21.0 years (interquartile range [IQR]: 10.0-34.0), and 62.1% were male. Overall guideline adherence of the administered prophylaxis was found to be 54.5%; among Category III/IV exposures with an indication for rabies immunoglobulin (RIG), RIG was administered in only 14.0% of cases. The vaccine series completion rate was 72.9%, and among the 14 variables examined, only a history of prior prophylaxis was found to be significantly associated with completion (p=0.014). Rural residence, atypical exposure types, and milder wound categories were associated with longer delays in presentation to the emergency department, and presentations increased markedly during summer months.Conclusion: Adherence of rabies post-exposure prophylaxis practices to national guidelines, particularly regarding the indication for rabies immunoglobulin, was found to remain below the desired level. Strengthening physician education and reviewing RIG accessibility in the region were considered necessary